Process optimization of vapour recompression (VRC) column for palm kernel oil (PKO) fatty acid fractionation - Sidek, Norul M.; Othman, Mohamad R. (AIP conference proceedings, 2023)
In the analysis of overall distillation column costs, energy usage has become the most essential element. Many researchers have focused on the development of external heat integration systems, such as heat pump assisted distillation, due to excellent performance in reducing net energy requirements. In regards to our previous works on this subject which showed only 50% of energy reduction, optimization might result in further energy saving. Therefore, this study intends to incorporate a two-step optimization procedure to the VRC-assisted column model for the fractionation of PKO fatty acid. The procedure includes the sensitivity analysis using Aspen Plus which went hand in hand with response surface methodology (RSM) using Design Expert. The optimal solution obtained from the RSM was validated in Aspen Plus to ensure model convergence. The superheated temperature and compression ratio were selected as the predominant factors to the exchanger duty. The model was found to be statistically significant, owing to its small p-value of <0.0001. The large R2 value of 97% suggests that the model was highly reliable in predicting the exchanger duty, which was proven from the small residual percentage of 6.14%. The given optimal point showed an increment of 27% of heat recovery from the top vapour stream. Though the results seemed appealing, the simulation of the optimal points in Aspen Plus revealed that the maximum allowable operating temperature was deviated.